Structural reconstruction strategies for the design of cellulose nanomaterials and aligned wood cellulose-based functional materials – A review. (1st November 2020) - Zhu, Zhaodong; Fu, Shiyu; Lavoine, Nathalie; Lucia, Lucian A.
Graphical abstract: Highlights: Structural reconstruction strategies for material design are concerned. The bottom-up principle of nanocellulose-based material assembly is analyzed. The top-down principle of wood-based material construction is summarized. The methodology of structural reconstruction is emphasized. Abstract: Cellulose is the world's most abundant natural polymer that displays highly desirable characteristics such as biodegradability and sustainability. Its derivatives and associated structured functional materials have potential in various fields such as surface engineering, energy and storage, water treatment, flexible electronics, construction, physical protection, and optical components. All of these applications demand nanocellulose-based micro/nano structural reconstruction for high performance. Recently, functional materials based on aligned nanocellulose in wood obtained through a top-down strategy have highlighted the importance of structure reconstruction strategies on functional designs. In this review, various cellulose or wood micro/nano materials designed by structure reconstruction were examined to highlight the importance of structure reconstruction strategies for various functionalities.